082 MRI for the detection of cerebral ischaemic events after transcatheter aortic valve replacement (TAVI). (22nd September 2015) - Fairbairn, T A; Goddard, A J P; Blackman, D; Plein, S; Greenwood, J P
Abstract : Background: Trans-catheter aortic valve implantation (TAVI) is a rapidly expanding treatment for patients with severe aortic stenosis who are considered too high risk for conventional surgical aortic valve replacement (AVR). Stroke is a recognised complication of TAVI with a reported incidence of 0.6–10%. Diffusion weighted MRI of the brain has demonstrated a high incidence of clinically silent white matter lesions (WML) post-cardiac catheterisation (∼15%) or cardiac surgery (CABG ∼31% and conventional AVR ∼33%). Our study aimed to determine the incidence of new WML detected by diffusion weighted MRI pre- and post-TAVI (18F CoreValve system). Methods: Fourteen patients underwent brain MRI scans immediately pre- and post-TAVI using a Phillips Intera 1.5Tesla scanner. The study was approved by the Leeds West Ethics Committee. Patients provided informed consent. Exclusion criteria were any contraindication to MRI (eg, permanent pacemaker). The MRI protocol included T2 Fast Field and Turbo Spin echo sequences and diffusion-weighted imaging. All scans were reported by a consultant neuroradiologist who was blinded to the clinical details. Results: All 14 patients (64% female, age 81±16 years) completed both brain diffusion weighted MRI scans pre- (median 1 day, IQR 1–1.75) and post- (median 5 days, IQR 5–7) TAVI. Nine patients (64%) developed at least one new lesion post-TAVI. In the 14 patients there were a total 26 new lesions, with a median new lesion count of 1 (range 0–9). All new lesions were small in size (<5 mm). Correlation to patient age (r=0.047) and pre-existing lesions (r=0.407) did not predict the incidence of new post-TAVI lesions. The lesions were single and multiple in a variety of locations (anterior circulation 46% / posterior circulation 54%). None of the patients had a clinically detectable stroke by neurological examination. Conclusions: Patients undergoing TAVI are high risk individuals with multiple co-morbidities and a high predicted mortality. Subclinical stroke post-cardiac catheterisation or cardiac surgery has been well reported to be associated with future neurocognitive decline. Our small cohort experienced new white matter lesions (infarction) in 64% of patients, double the reported conventional surgical AVR rate, although by definition TAVI patients are much higher risk. Given the increasing survival and longevity of these patients this could have future implications on quality of life, post-operative cognition and cost (QALY's).